HUBUNGAN FAKTOR LINGKUNGAN DAN FAKTOR PERILAKU DENGAN KEJADIAN DEMAM BERDARAH DENGUE (DBD) DI WILAYAH KOTA SEMARANG - Evy Ratnasari; Onny Setiani; Hanan Lanang Dangiran (Jurnal Kesehatan Masyarakat (Undip), 2018)
DHF often cause outbreaks and releated to the environment. IR reached in West Semarang Sub Disrict is 17,05 per 100.000 population dan IR reached in North Semarang is 15,08 per 100.000 population. This research had purposes to analyze therelationship between environmental and behaviors factors with the incidence of Dengue Hemorrhagic Fever (DHF) in the West Semarang and North Semarang Subdistricts of Semarang City. This research was an observational analytic research applying case control design. In this research, the sample criterias were case sample and control sample. The total members of case sample were 43 members and for control members were 43 members. The case samples were DHF patients from January 2017-Febuary 2018 who living in West Semarang and North Semarang Sub Districts and the case control were the neighbors who are not infected by DHF. Data were anayzed in univariate and bivariate using Chi Square. Univariat analysis showed analysis of indoor and outdoor temperature was obtained homogeneous result, 1,2% risk of indoor humidity, outdoor humidity showed analysis was obtained homogeneous result, 76,7% of high population density, 70,9% risk presence of vegetation, 40,7% risk of standing water, 2,3% poor knowledge, attitude showed analysis was obtained homogeneous result and 67,4% poor practice. This research found that there was a association between the standing of water (p=0,000), and practice (p=0,001) with  the dengue case. There is no a relationship between indoor humidity (p=0,314), population density (p=1,000), presence of vegetation (p=0,235) and knowledge (p=1,000) with dengue case.